2010
DOI: 10.1002/macp.200900436
|View full text |Cite
|
Sign up to set email alerts
|

New Generation of Polymeric Drugs: Copolymer from NIPAAM and Cyclodextrin Methacrylate Containing Supramolecular‐Attached Antitumor Derivative

Abstract: We describe the synthesis of an adamantane‐bearing analogue of 5‐fluorocytosine. The process was investigated by 1H NMR, FT‐IR spectroscopy, MS‐EI mass spectrometry and elemental analysis. The non‐covalent inclusion complexation of the synthesized compound with a copolymer containing NIPAAM and cyclodextrin methacrylate was investigated by turbidity measurement, dynamic light scattering, and UV–Vis spectrofotometry.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…Complex 21 of adamantane-containing 5-fluorouracil analog 22 and cyclodextrin-containing copolymer 23 was prepared [17]. The complex was formed via noncovalent inclusion of adamantane moieties into cyclodextrin cavities.…”
Section: A-imentioning
confidence: 99%
“…Complex 21 of adamantane-containing 5-fluorouracil analog 22 and cyclodextrin-containing copolymer 23 was prepared [17]. The complex was formed via noncovalent inclusion of adamantane moieties into cyclodextrin cavities.…”
Section: A-imentioning
confidence: 99%
“… ðàáîòå [17] áûë ïîëó÷åí êîìïëåêñ 21 àäàìàíòàíñîäåðaeàùåãî àíàëîãà 5-ôòîðóðàöèëà 22 ñ öèêëîäåêñòðèíñî-äåðaeàùèì ñîïîëèìåðîì 23. Îáðàçîâàíèå êîìïëåêñà ïðîèñõîäèò çà ñ÷åò íåêîâàëåíòíîãî âêëþ÷åíèÿ àäàìàíòàíî-âûõ ôðàãìåíòîâ ìîëåêóëû â öèêëîäåêñòðèíîâûå ïîëîñòè.…”
Section: ãðóïïàunclassified
“…An in vitro study showed that the DOX-loaded nanoparticles could release their payload in response to the endosomal-pH after being internalized by HeLa cells via a nonspecific endocytosis pathway. 59 2.3.2 Conjugation of CD derivatives to pre-existing polymers. 56 To obtain pure mono-vinyl substituted CD monomers, an improved method was reported further by the same group.…”
Section: Cd-pendant Polymersmentioning
confidence: 99%